The yellow pigment in Portuguese 17th century azulejos - Coentro, S. (2011)
The Naples Yellow pigment (lead antimonite) and its variants ((Pb-Sb-Sn and/or Pb-Sb-Zn triple oxides) have been the subject of several studies in the last decade [1-3]. This study focuses on the chemical characterization of the yellow pigment used by Portuguese historic glazed tile makers in the 17th century, using non-destructive techniques. Special attention was given to understanding of the production techniques at the time, namely the pigment synthesis and its posterior modifications occurred during the firing of the glaze.